The Effect of Democratic Leadership Style, Compensation and Work Motivation on Job Loyalty with Job Satisfaction as an Intervening Variable: Pengaruh Gaya Kepemimpinan Demokratis, Kompensasi dan Motivasi Kerja Terhadap Loyalitas Kerja dengan Kepuasan Kerja Sebagai Variabel Intervening - Auliyah, Leni Mega; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine the effect of Democratic Leadership Style, Compensation and Work Motivation on Job Loyalty with Job Satisfaction as an Intervening Variable at PT. Sriwijaya Air. The sample in this study employees at PT. Sriwijaiya Air, totaling 65 people. The sampling technique uses the accidental sampling method, which is a technique for determining the sample based on chance. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity testing and reliability testing. To test the hypothesis in this study using path analysis. The results of this study indicate that (1) Democratic leadership style has an effect on job satisfaction at PT. SriwijayaAir. (2) Compensation has no effect on job satisfaction at PT. Sriwijaya Air. (3) Work motivation has an effect on job satisfaction at PT. Sriwijaya Air. (4) Democratic leadership style has no effect on work loyalty at PT. Sriwijaya Air. (5) Compensation has no effect on work loyalty at PT. Sriwijaya Air. (6) Work motivation has no effect on work loyalty at PT. SriwijayaiAir. (7) Job satisfaction has an effect on job loyalty at PT. Sriwijaya Air. (8) Democratic leadership style has an effect on job loyalty with job satisfaction as an intervening variable at PT. Sriwijaya Air. (9) Compensation has no effect on job loyalty with job satisfaction as an intervening variable at PT. Sriwijaya Air. (10) Work motivation has an effect on job loyalty with job satisfaction as an intervening variable at PT. Sriwijaya Air.